Nano-welding and junction formation in hydrogen titanate nanowires by low-energy nitrogen ion irradiation. (20th May 2015) - Dhal, Satyanarayan; Chatterjee, Shyamal; Sarkar, Subhrangsu; Tribedi, Lokesh C; Bapat, Rudheer; Ayyub, Pushan
Abstract: Crystalline hydrogen titanate (H2 Ti3 O7 ) nanowires were irradiated with N + ions of different energies and fluences. Scanning electron microscopy reveals that at relatively lower fluence the nanowires are bent and start to adhere strongly to one another as well as to the silicon substrate. At higher fluence, the nanowires show large-scale welding and form a network of mainly 'X' and 'Y' junctions. Transmission electron microscopy and Raman scattering studies confirm a high degree of amorphization of the nanowire surface after irradiation. We suggest that while ion-irradiation induced defect formation and dangling bonds may lead to chemical bonding between nanowires, the large scale nano-welding and junction network formation can be ascribed to localized surface melting due to heat spike. Our results demonstrate that low energy ion irradiation with suitable choice of fluence may provide an attractive route to the formation and manipulation of large-area nanowire-based devices.